Is it possible for a Procellariiform to raise two chicks? A case of chick adoption in Southern Giant petrels Macronectes giganteus in the South Shetland Islands, Antarctica - Archuby, Diego Ignacio (2010)
We report on the adoption of a Southern Giant Petrel Macronectes giganteus chick by a breeding pair on 25 de Mayo Island (King George Island), South Shetland Islands, Antarctica. Our observations showed both chicks received similar amounts of food, but there were differences in their growth rates that could be explained by their gender. After the third week of adoption, aggressive behaviors were common between chicks, usually expressed through regurgitation. This resulted in a low rate of growth in both chicks. Neither chick fledged, and both were found dead near the colony seven weeks after adoption. The constant fights between them could be one of the causes of their death, particularly if death resulted from excessive regurgitation. Although exclusion of unrelated chicks at nest sites has not been reported in M. giganteus, chick adoption seems to have no clear benefits and may contribute to brood failure.